The potential mechanisms and regulatory roles of exosomal miRNA in neural repair after spinal cord injury - Shi, Yuanhu; Li, Zhilong; Pu, Yuanxu; Wang, Qinghua; Cui, Zhiming; Qi, Longju; Sun, Yuyu (Frontiers in Cellular Neuroscience, 2026)
Spinal cord injury (SCI) is a devastating disorder of the central nervous system. It is characterized by primary mechanical damage and secondary pathological cascades. These lead to persistent sensory and motor deficits, substantial socioeconomic burdens, and limited therapeutic efficacy. Exosomes are nanoscale vesicles secreted by various cells that serve as key mediators of intercellular communication by delivering bioactive molecules, particularly microRNAs (miRNAs), which regulate gene expression in target cells. This review explores how exosomal miRNAs contribute to neural repair in SCI. These contributions include inhibiting neuroinflammation via pathways such as NF-κB and TLR4; suppressing neuronal apoptosis through PTEN/PI3K/Akt signaling; promoting axonal regeneration via the ERK1/2/STAT3 and NGF/TrkA pathways, enhancing angiogenesis by targeting SPRED1 and integrin α5, and modulating of the immune microenvironment toward M2 polarization, and multifaceted neuroprotection involving alleviating autophagy and endoplasmic reticulum stress. Drawing on recent preclinical studies from 2024–2025, including those utilizing mesenchymal stem cell–derived exosomes loaded with miRNAs such as miR-124-3p, miR-338-5p, and miR-216a-5p, the review highlights promising innovations, such as bioengineered exosomes and biomaterial integrations. Recent preclinical advancements, such as exosome-based therapies that have shown reduced lesion volumes and improved motor function in rodent models, highlight the potential for translation to clinical applications. Ongoing efforts are anticipated to lead to clinical trials in the near future. Despite challenges in standardization, delivery efficiency, immunogenicity, and long-term safety, exosomal miRNA therapy offers a cell-free, multitargeted approach with strong potential for clinical translation in SCI management.